The Impact of Embryo Storage Time on Pregnancy and Perinatal Outcomes and the Time Limit of Vitrification: A Retrospective Cohort Study - Cui, Mengge; Dong, Xiyuan; Lyu, Shuhao; Zheng, Yu; Ai, Jihui (Frontiers in Endocrinology, 2021)
Background: The technique of embryo cryopreservation has been increasingly applied in clinical settings. However, there has been a concern about the safety and efficacy of long-term freezing of embryos. Therefore, the aim of this study was to evaluate whether storage time of vitrification had any effects on pregnancy as well as perinatal outcomes, further, to explore the appropriate time limit of vitrification. Methods: The study included women who underwent at least one frozen-thawed cycle with single embryo transfer between January 1st, 2016 and September 30th, 2019. Patients were assigned into 3 groups according to the storage time (<3 months, 3-12 months and >12 months) to evaluate the impact of embryo storage time on pregnancy and perinatal outcomes. To further investigate the time limit of vitrification, propensity score matching was used to compare the primary outcomes of patients with storage time of 1-3 years, 3-5 years, and >5 years to those stored for ≤1 year. Results: A total of 9806 frozen-thawed embryo transfer cycles were included in our study. After adjustment for confounding variables, no significant differences were found in pregnancy outcomes among groups. However, postponement of transfer increased the risks of large for gestational age and placenta previa. In addition, after propensity score matching, 171 cycles with storage time >5 years were matched with those ≤1 year, both the clinical pregnancy rate and live birth rate decreased significantly when the storage time exceeded 5 years. Conclusions: The duration of vitrification did not significantly affect the pregnancy outcomes within 5 years period. However, the clinical pregnancy rate and live birth rate both decreased significantly when the duration of vitrification exceeded 5 years. It is worth noting that the conclusion was drawn from a small sample study after propensity score matching and should be treated with caution. In addition, the cycles were from different time periods, which could have an impact on the results.